Why are the policies and organisations seeking to help disabled people access work failing? - Stafford, B. (Policy Press, 2015)
In recent years successive governments, through the responsible department, the Department for Work and Pensions (DWP), have implemented programmes that involve private and third sector organisations competitively tendering to deliver programmes targeted at working age people including disabled people. Typically, however, these initiatives have only relatively small impacts on employment. This is not to deny that employment programmes have successfully placed some disabled people in employment rather to argue that the people most in need of support are the least served by these programmes. This occurs because the contracts have an incentive structure that rewards contractors for working with, and placing in employment, participants who are more job ready. Providers are then more likely to meet performance targets, and importantly for their finances, generate revenue income. Two examples of these programmes – the New Deal for Disabled People (NDDP) and Pathways to Work (Pathways) – are presented in this chapter to illustrate the argument that the marketisation of such provision can disadvantage many disabled people in the labour market.